(untitled) (Bangladesh Journal of Scientific Research, 2018)
This study, employing a logistic regression model seeks to identify the important factors that influence household’s access to banking services. The result shows that about 31.7% households have bank account while the remaining 68.3% households have no such account. The result found that with the increase in age of household’s head access to banking services increased gradually. As observed, female headed household have greater access to banking services as compared to male headed household. More so, formerly/ever married headed households have less access to banking services by comparison with never married headed households. The result also shows that access to banking services gradually increased with increasing education level of household’s head. It is found that poor households have very less access to banking services as compared to non-poor households. Increased land ownership of household allowed gradual increase in the access to banking services. The result also mentions that nonowner homestead households have less access to banking services as compared to own homestead households. According to the logistics regression analysis, comparing with the rural households it has been found that the urban households have more access to banking facilities. Bangladesh J. Sci. Res. 30(1&2): 81-89, December-2017